Consumer Purchasing Decision towards Skin Care Products - Abarna K; Aishwarya Devi C V; Ashwathy P Sathyan; Dr. Poongodi B (International Journal of Engineering and Management Research, 2022)
The global trend of using skin care products is growing at accelerator rate. As a result of which number of skin care products are emerging as consumer options. The purpose of this study is to analyse the factors influencing consumers decision to purchase skin care products. The study is about the purchasing pattern of people in and around Coimbatore city. A self- designed questionnaire has been designed to collect the information from the respondent. Around 120 samples have been collected for this research. For identifying the purchasing behaviour of the consumer, the respondent was asked to rank the variables based on the Likert scale. The influence of social media on consumer behaviour is also analysed. The statistical analysis that has been done is regression. The insights gained will help the skin care marketers to develop the better growth strategy to sustain the market. This study provides the better understanding of how different variables influence purchasing behaviour.